2020
DOI: 10.3389/fmicb.2020.00375
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Host Evolution of Norovirus GII.4 in a Chronic Infected Patient With Hematopoietic Stem Cell Transplantation

Abstract: Human noroviruses (NVs) are the leading cause of acute gastroenteritis outbreaks worldwide. The majority of outbreaks are caused by genogroup II.4 (GII.4), with new variants emerging every 2 to 4 years. Immunocompromised patients are hypothesized to be important reservoirs where new NV variants emerge. Here, we examined intrahost NV variants and assessed immune-driven NV evolution in chronically infected immunocompromised hosts. Three NV GII.4-positive samples were collected from the same patient in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Noroviruses have been detected in previously unrecognised host species [18,19]; detection itself is facilitated by the novel analytical techniques that increasingly supplement established molecular methods [259,[261][262][263]265]. New potential HuNoV transmission routes and/or viral reservoirs have been postulated [223,230,233]. Recent in vivo and in vitro findings have added to the understanding of host immunity in response to norovirus infection [272][273][274].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Noroviruses have been detected in previously unrecognised host species [18,19]; detection itself is facilitated by the novel analytical techniques that increasingly supplement established molecular methods [259,[261][262][263]265]. New potential HuNoV transmission routes and/or viral reservoirs have been postulated [223,230,233]. Recent in vivo and in vitro findings have added to the understanding of host immunity in response to norovirus infection [272][273][274].…”
Section: Discussionmentioning
confidence: 99%
“…Not only has the involvement of chronic shedders in hospital outbreaks indicated them to be a reservoir for nosocomial transmission of noroviruses [146], but persistently infected patients have also been suggested to contribute to HuNoV transmission as reservoirs for emerging strains. Intra-host evolution via point mutation accumulation [230,231] and the acquisition of superinfections over the protracted period of persistent infections [143] implicate persistently infected patient cohorts as potential reservoirs for novel HuNoV variants [213]. Multiple phylogenetic analyses have identified viral populations in persistently infected patients to be highly diverse and genetically distinct from viruses circulating in the general population [147,232].…”
Section: Reservoirsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phase-III trials of coronavirus disease 2019 (Covid-19) vaccines had shown high preventive efficacy against symptomatic infection and acceptable safety profile in a record time, yet their public acceptance would be an essential deterrent to pandemic control [ 1 ]. The hesitancy to a safe and effective vaccine against a severe infection is a major global health threat and commonly referred to as the “pandemic public health paradox”, previously well-observed with influenza [ 2 , 3 ]. Healthcare personnel (HCP) are among the first to receive the Covid-19 vaccination.…”
mentioning
confidence: 99%
“…The non-structural protein, p22, and structural protein VP2 are likely to influence the replication process with roles in antagonism of protein secretion [33] and host cell entry [34], respectively. It is notable that none of the non-synonymous minor variants observed during chronic infection were found in ORF2, given the breadth of literature reporting minor variants or amino acid fixations in epitopes or putative epitope sites in VP1 during chronic infection [24,29,35,36]; however, these studies sampled over a much longer period (76-1811 days). Distinct antigenic types of HuNoV have been reported to emerge over the course of chronic infection, leading to predictions that changes occurring in immunodominant epitopes could lead to evasion of population humoral immunity, and subsequent strain emergence [37,38].…”
Section: Discussionmentioning
confidence: 99%